Hak Kebebasan Berekspresi Sebagai Hak Konstitusional: Analisis Normatif Berdasarkan Uud 1945 dan Teori Konstitusi - Yetti Octavianingsih; Rachmat Abdillah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The right to freedom of expression including artistic expression as a constitutional right guaranteed in the 1945 Constitution, especially Articles 28E and 28F. Critical artworks are often restricted through legal or social pressures, creating a gap between normative and practical restrictions in the field. Cases in Indonesia show that artworks are often the object of silencing that has the potential to violate constitutional principles. The right to freedom of expression as part of civil and political rights is an affirmation that freedom of expression is not only important for individuals, but also the main foundation for a healthy democracy. Understanding is needed from policy makers, law enforcement officers, and civil society in implementing the principle of restrictions in accordance with the constitution and international human rights norms. Progressive constitutional interpretation and institutional strengthening are needed so that critical expression is not silenced by multi-interpretable legal norms, so that freedom of expression in order to realize a healthy public space in a democratic state of law must be maintained as a fundamental right.